Size effect of typical hygrothermal properties test values for building insulation materials - Yang, Wen; Zhang, Guanjie; Wen, Jun; Zhou, Chengyan; Liu, Jiaping (Energy and buildings, 2024)
[Display omitted] Thermal and moisture properties of building insulation materials are crucial input parameters for analyzing thermal and moisture transfer phenomena in building environments. Accurate determination of these parameters under different conditions is essential for the correct application and assessment of materials and envelope structures. However, numerous factors influence thermal and moisture properties, and while extensive research has been conducted on this topic, the effects of specimen size on typical thermal and moisture property test values remain unclear. To address the issue of unreliable data caused by random specimen sizes in thermal and moisture property testing of building insulation materials, this study selects three materials—expanded polystyrene (EPS), extruded polystyrene (XPS), and foamed cement—as test subjects to explore the size effects on typical thermal and moisture property test values. The results indicate that specimen size significantly affects the test values for typical thermal and moisture properties, with only a few experiments showing negligible size effects for certain materials. For foamed cement, recommended specimen sizes for thermal conductivity testing using the guarded hot plate method and the transient plane source method are 300 × 300 × 30 mm and 50 × 50 × 30 mm, respectively. Except for equilibrium moisture absorption experiments, the weight of other moisture property tests is generally represented by thickness > planar dimensions.